Comparative productive performance of cows born through embryo transfer, artificial insemination and natural mating in dairy and dual-purpose herds raised in tropical conditions - Martínez, J. F. (2023)
A populational, observational and longitudinal-retrospective study with records of 28 dairy-specialized and dual-purpose farms was carried out to compare the productive performance of cows born by embryo transfer (ET), artificial insemination (AI) and natural mating (NM), using the database of Centro Regional de Investigación para la Producción Animal Sostenible (CRIPAS) of cattle herds in Costa Rica. Herds (system × altitude), conception method (ET, AI and NM), genetic background (DSpB: special- ized dairy breeds [Bos taurus] and crosses, GYR × HOL: Gyr × Holstein Crossbred and DSpB × BI: crosses between dairy breeds and Bos indicus), year of birth (or at calv- ing), lactation number and days in milk were evaluated for the productive parameters age at first calving (AFC), calving to conception interval (CCI) and lactation milk yield (LMY) using a GLIMMIX procedure on SAS. The AFC, CCI and LMY were affected (p< .0001) by all factors considered in each parameter. ET has lower (p< .0001) AFC in months (33.1) than AI (35.2) and NM (36.44). NM had lower (p= .004) CCI (110 days) than AI or ET (121 days) values which were similar (p> .05). The higher LMY (p< .0001) was observed in ET (4140 kg), compared to AI (3706 kg) and NM (3595 kg). There was no difference between AI and NM. In conclusion, the method of conception in calves affected their future reproduction and production during puberty, postpartum and lactation. The effects on management decisions will require a rigorous economical study to discern whether ET would be a cost-effective alternative to AI or NM.